The impact of e-books on the Brazilian publishing supply chain: An exploratory analysis - Fernando Coelho Martins Ferreira; Luis Fernando Moreira Miranda; Monique Moras (RAE: Revista de Administração de Empresas, 2018)
This work aims to analyze the main effects of the emergence of electronic books within the context of the Brazilian publishing supply chain. Interviews with executives from publishing groups in the country have made it possible to identify that e-books still play a minor role in the publishing supply chain, and are more likely to thrive in specific book genres. Electronic books have not made this chain leaner. Since e-books did not replace physical books and instead coexisted with them, publishers were obliged to develop a new set of activities within the existing publishing supply chain. Disintermediation is one of the most striking features of this new production process. In order to adapt to this new scenario, the publishing sector needs to implement adjustments that extend beyond its typical operations, which also implies the need for a redefinition of resources and development of requisite competencies.